The evolution of classification and technical rules in parasports: extending the frontiers - Evgeny Mashkovskiy; Ian Brittain (Karolinum Press, 2017)
The aim of this paper is to elaborate on some of the factors that may influence the evolution of classification and technical (C&T) rules in parasports and highlight the often complex nature of these influences. Potential factors include an increase in the range of impairment types participating in particular sports, the fairness and transparency of C&T rules and media portrayal/ explanation of them and the impact of inclusion practices in sport, both of disabled athletes into non-disabled sport as well as non-disabled athletes taking part in parasports. The role of technology in parasport is also discussed, as are the challenges of changing or introducing new C&T rules, especially with respect to their potential impact upon financial and sports management aspects of parasports. The paper concludes by suggesting a possible decision making model for the future development of new C&T rules.